Erotically Queer A Pink Therapy Guide for Practitioners - Neves, Silva; Davies, Dominic (Taylor & Francis, 2023)
Erotically Queer is a practice guide for clinicians, bringing together experts in their field with pioneering topics within GSRD (gender, sex and relationship diversity). Chapters cover an array of topics rarely discussed in either clinical or popular literature including lesbian sex, queer menopause, bisexuality, working with shame, the sex lives of asexuals, sexuality and transgender people, treating anodyspareunia, compulsive sexual behaviours and chemsex. It also helps practitioners reflect on their biases regarding BDSM/kink and understand more regarding non-pathologising practices with intersex people. The book aims to help all clinicians work more effectively with the Queer population, with the most contemporary sexological knowledge.